Clinical Characteristics of Concomitant Systemic Lupus Erythematosus and Primary Biliary Cirrhosis: A Literature Review - Toru Shizuma (Journal of Immunology Research)
Although autoimmune diseases often coexist, concomitant cases of systemic lupus erythematosus (SLE) and primary biliary cirrhosis (PBC) are uncommon. In this review paper, 34 cases of SLE with concomitant PBC found in English and Japanese scientific literature and Japanese proceedings were reviewed and summarized, including cases with liver dysfunction complicated by SLE. Of the 34 reported concomitant cases of SLE and PBC, 97.1% (33/34) were females, and PBC was diagnosed initially in 69.0% (20/29), except for five cases in which both SLE and PBC were simultaneously diagnosed. Sjögren’s syndrome was the most common autoimmune disease complicating concomitant SLE and PBC (23.5%, 8/34). Five deaths have been reported: two elderly patients died of liver failure because of the worsening of PBC, and another two patients died from pulmonary infection associated with SLE pharmacotherapy. It is uncertain whether concomitant cases occur by chance or share a common immunological or genetic basis.